The nicotinamide ruthenium(II) complex induces the production of reactive oxygen species (ROS), cell cycle arrest, and apoptosis in melanoma cells. (1st February 2023) - Silva, Henrique Vieira Reis; da Silva, Guilherme Álvaro Ferreira; Zavan, Bruno; Machado, Rafael Pereira; de Araujo-Neto, João Honorato; Ellena, Javier Alcides; Ionta, Marisa; Barbosa, Marília Imaculada Frazão; Doriguetto, Antônio Carlos
Graphical abstract: New complexes with the general formula [RuCl(NIC)(dppb)(X-bipy)]PF6 were prepared by exchanging the Cl - trans ligand to the phosphorus atom by Nicotinamide (NIC). DNA and human serum albumin interactions were evaluated. Compound C3 showed high activity and selectiveness in WM1366 tumor lines, SK-MEL-147 and mainly CHL-1. Which were correlated to the generation of species that react to oxygen (ROS). Abstract: A set of new ruthenium complexes, [RuCl(NIC)(dppb)(4, 4′-Me-bipy)]PF6 (C1 ), [RuCl(NIC)(dppb)(4, 4′-Methoxy-bipy)]PF6 (C2 ), and [RuCl(NIC)(dppb)(5, 5′-Me-bipy)]PF6 (C3 ), where NIC = 3-pyridinecarboxamide, 4, 4′-Me-bipy = 4, 4′-dimethyl-2, 2′-bipyridine, 4, 4′-Methoxy-bipy = 4, 4′-dimethoxy-2, 2′-bipyridine, and 5, 5′-Me-bipy = 5, 5′-dimethyl-2, 2′-bipyridine were synthesized and characterized by elemental analysis, UV/Vis and infrared spectroscopy, 31 P 1 H, 1 H, 13 C 1 H nuclear magnetic resonance (NMR), and cyclic voltammetry. In addition, the structure of [RuCl(NIC)(dppb)(4, 4′-Me-bipy)]PF6 was confirmed by single crystal X-ray diffraction (XRD). The solution stability study of C1-C3 showed the formation of pyridine which was coordinated due to solvent protic attacked to nicotinamide, and an elimination reaction of a carbamate group was observed. C1 -C3 interacted with DNA through intercalation, electrostatic forces of attraction, or hydrogen bonding. The complexes interacted, moderately and spontaneously, with HSA, mainly through Van der Waals and hydrogen bond interactions. An in vitro evaluation of the (C1-C3 ) complexes revealed a cytotoxicity against MCF-7, HepG2, A549, SK-MEL-147, WM1366, and CHL-1. A higher cytotoxicity was observed for compound (C3 ) against melanoma cell cancer (CHL-1). Moreover, the (C3 ) complex inhibited the clonogenic capacity and cell cycle progression of CHL-1 cells and induced apoptosis involving the production of reactive oxygen species (ROS). [RuCl(py)(dppb)(5, 5′-Me-bipy)]PF6 presented a very close C3 cytotoxicity against melanoma cell cancer (CHL-1).